A generalized XFEM procedure for analyzing intersecting joints in rock masses with excavation. Issue 3 (5th May 2015) - Deb, Debasis; Pramanik, Ranjan; Das, Kamal Ch
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse of structures made in rock mass with multiple intersecting discrete discontinuities such as joint, fault, shear plane. Design/methodology/approach – In this study, a numerical method is proposed for analyzing multiple intersecting joints with varying dip angles, spacing and roughness in eXtended Finite Element Method platform. A procedure is also outlined to treat excavated enhanced (jointed) elements for analysing the effect of excavation sequences. Findings – The proposed method is compared with the existing interface element methods (Phase-2 model) by considering the stress and displacement distributions of a multiple intersecting jointed rock sample under uniaxial loading conditions. A circular tunnel in rock mass having intersecting joints is also analyzed for the distribution of mobilised friction angle of joints and results are compared with a derived analytical solution. Research limitations/implications – Nucleation and propagation of cracks should be incorporated into the proposed framework in future studies. Practical implications – The proposed method is a useful tool for rock mechanics and geotechnical engineering problems to analyse strength and deformability of jointed rock masses. Originality/value – The paper enumerates concepts and detail implementation procedures of the proposed method in three-noded triangular elements. The intersection of joints is formulated in such a way that no additional (junction) enrichment is required in model. The method has been improved for inclusion of Dirichlet and Neumann boundary conditions to be applied in the enhanced part of a problem domain.